Analisis Hubungan Perilaku Merokok dengan Harga Diri Mahasiswa Fakultas Ilmu Keperawatan - Jian Ahmad Inzagi; Nutrisia Nu’im Haiya; Iwan Ardian (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Self-esteem is an important aspect of mental health that reflects how individuals value and appreciate themselves. Various factors such as social environment, academic demands, and lifestyle behaviors like smoking can influence self-esteem levels. Among nursing students, smoking behavior is considered contradictory to the values of the nursing profession, which emphasizes health promotion. This study aimed to determine the relationship between smoking behavior and self-esteem among students of the Faculty of Nursing, Sultan Agung Islamic University. This study employed a quantitative method with a correlational design and a cross-sectional approach. The population consisted of 84 male students of the Faculty of Nursing, selected using stratified purposive sampling. Data were collected using a smoking behavior questionnaire and the Rosenberg Self-Esteem Scale (RSES). Data analysis was conducted using the Chi-Square test. The findings indicated that most students were non-smokers and had a moderate level of self-esteem. The Chi-Square test showed a significant relationship between smoking behavior and self-esteem (p < 0.05), where students who smoked tended to have lower self-esteem than non-smokers. There is a significant relationship between smoking behavior and self-esteem among students of the Faculty of Nursing, Sultan Agung Islamic University.